2015
DOI: 10.1111/pace.12588
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic Events 7–11 Years after Catheter Ablation of Atrial Fibrillation

Abstract: Our study shows low TE rates 9 years after ablation of AF that are lower than published data for AF patients with anticoagulation only. AF patients with a CHA2DS2-VASc ≥2 should, however, be maintained on anticoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The authors concede that the very low stroke rate could have been the outcome of successful ablation and freedom from AF in the majority of patients. A body of evidence now points to catheter ablation therapy for AF conferring stroke risk reduction [21] , [22] . However, AF recurrence, cardiovascular morbidity, and stroke, are still observed to correlate with CHA 2 DS 2 -VASc score of 2 or greater over long-term follow-up [21] , [22] , [23] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concede that the very low stroke rate could have been the outcome of successful ablation and freedom from AF in the majority of patients. A body of evidence now points to catheter ablation therapy for AF conferring stroke risk reduction [21] , [22] . However, AF recurrence, cardiovascular morbidity, and stroke, are still observed to correlate with CHA 2 DS 2 -VASc score of 2 or greater over long-term follow-up [21] , [22] , [23] .…”
Section: Discussionmentioning
confidence: 99%
“…A body of evidence now points to catheter ablation therapy for AF conferring stroke risk reduction [21] , [22] . However, AF recurrence, cardiovascular morbidity, and stroke, are still observed to correlate with CHA 2 DS 2 -VASc score of 2 or greater over long-term follow-up [21] , [22] , [23] . The stroke rate in the current study compares similarly with the 0.72% event rate at mid-term follow-up of a large cohort of patients on anticoagulants with a mean CHA 2 DS 2 -VASc score of 2.1±1.4 from the Leipzig Heart Center AF Ablation Registry [22] and contrasts with a much higher reported event rate of 5.1% for patients with CHA 2 DS 2 -VASc score of 2 who did not receive anticoagulation over a follow-up period of 39 months following catheter ablation [23] .…”
Section: Discussionmentioning
confidence: 99%
“…The small subset of writing group members who support the discontinuation of systemic anticoagulation in patients with an increased stroke risk profile make the argument that (1) continuing anticoagulation exposes patients to the risks for hemorrhage and the unfavorable effects of anticoagulation on long-term QOL; (2) several large outcome studies have reported a lower-than-expected stroke risk in patients who undergo AF ablation compared with control populations 239 ; and (3) one center has reported a low stroke risk in patients postablation who screen for recurrence by pulse assessment or ECG monitoring. 238 , 407 , 409 , 545 , 856 , 857 , 858 , 859 , 860 …”
Section: Section 7: Technical Aspects Of Ablation To Maximize Safety mentioning
confidence: 99%
“…The small subset of writing group members who support the discontinuation of systemic anticoagulation in patients with an increased stroke risk profile make the argument that (1) continuing anticoagulation exposes patients to the risks for hemorrhage and the unfavorable effects of anticoagulation on long-term QOL; (2) several large outcome studies have reported a lower-than-expected stroke risk in patients who undergo AF ablation compared with control populations 239 ; and (3) one center has reported a low stroke risk in patients postablation who screen for AF recurrence by pulse assessment or ECG monitoring. 238 , 407 , 409 , 545 , 856 , 857 , 858 , 859 , 860 …”
Section: Section 7: Technical Aspects Of Ablation To Maximize Safety mentioning
confidence: 99%